Pengaruh Pemberian Limbah Batang Buah Naga Terhadap Kualitas Kompos Feses Sapi - Jalius Jalius; Dody Aji Kurniawan; Fachroerozi Hoesni; Firmansyah Firmansyah (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
This study aims to determine the best level of administration of dragon fruit stem waste on the quality of cow feces compost. The design used was a completely randomized design (CRD) with 5 treatments and 4 replications. The treatments consisted of P0 = cow feces 97.5% + EM4 2.5%, P1 = cow feces 77.5% + dragon fruit stem waste 20% + EM4 2.5%, P2 = cow feces 67.5% + waste dragon fruit stem 30% + EM4 2.5%, P3 = cow feces 57.5% + dragon fruit stem waste 40% + EM4 2.5, P4 = cow feces 47.5% + dragon fruit stem waste 50% + EM4 2.5%. The observed variables were color, odor, texture, temperature, pH, nitrogen, carbon, phosphorus, potassium and C/N ratio. The results showed that the colors produced in the treatment were P0 (100% black), P1 (100% black), P2 (100% black), P3 (50% black chocolate and 50% brown), P4 (100% chocolate). The odor produced in the treatment of P0 (100% soil), P1 (75% soil and 25% weathered), P2 (50% weathered and 50% weathered), P3 (100% weathered), P4 (100% weathered). The resulting texture in the treatment of P0 (100% crumb), P1 (100% crumb), P2 (100% crumb), P3 (50% crumb and 50% coarse), P4 (75% coarse and 25% crumb), pH value in treatment P0 (7.23%). The addition of dragon fruit stem waste had a very significant effect (P<0.01) on the content of nitrogen, phosphorus, potassium and C/N. The highest nitrogen content was at P2 (1.60%) and the lowest was at P0 (1.31%), the highest phosphorus content was at P4 (0.31%) and the lowest was at P0 (0.18%), the highest potassium content was found in at P3 (1.16%) and the lowest at P0 (0.44%), the highest C/N content was at P0 (22.25%) and the lowest was at P3 (16.75%). Meanwhile, the carbon content had no significant effect (P>0.05). From the results of this study, it can be concluded that the best compost quality results were obtained in treatment (P3), on the content of carbon, potassium and C/N. Because it is based on the standard range of compost quality (SNI 19-7030-2004).